The macrobenthic community along a mercury contamination in a temperate estuarine system (Ria de Aveiro, Portugal) - Nunes, M. (2008)
Mercury is a widely distributed environmental pollutant and a toxic element to all living organisms. This study represents an attempt to evaluate its correlation with the macrobenthic community structure in a temperate estuarine system, the Ria de Aveiro (Portugal). The macrobenthic community structure showed significant differences along the mercury gradient. Overall, the increase of mercury contamination was associated with reduced total abundance, lower species richness, and dominance of tolerant taxa. The polychaetes Hediste diversicolor and Alkmaria romijni, and the isopod Cyathura carinata were associated with high levels of mercury in sediment, while the bivalves Scrobicularia plana, Cerastoderma edule and Abra alba showed higher density in lesser contaminated sites. Furthermore, highly contaminated sites showed substantially lower abundances of surface-deposit feeders and herbivores, and higher abundances of subsurface-deposit feeders and omnivores. Salinity was also a significant factor affecting the community, being responsible for seasonal variations in the macrobenthic assemblages.